KASUS CYBERCRIME DI INDONESIA - Dista Amalia Arifah (Jurnal Bisnis dan Ekonomi, 2011)
At the beginning was found, Computer is a huge machine with limited ability, but in recent years after manyupgrade and update Computer become a popular machine which many ability, men become amused and addictwith It. Moreover when internet was invented, Computer development going rapidly than years. There are somuch Internet advantage,otherwise threatened by danger, Crime over Internet or known with Cybercrime, whichare take many form through; virus, denial of service etc. Damage caused by Cybercrime was uncountableanymore but specific law related to Cybercrime in Indonesia wasn’t ready yet. Any article found in inner partand outer part of Indonesian Criminal Code (KUHP) can be used to the crime related computer or Internet butnot to all kinds. The barrier of Cybercrime investigation process connect to the rules, law officer ability,evidence and supporting facilities. Some problem solving to overcome Cybercrime investigation should be takenlike: completing Cybercrime rules, hold Cybercrime training continuosly for law officer and build specificCybercrime investigation division also campaign Cybercrime prevention widely among citizen.Key words : computer, Internet, Cybercrime, Hacker, law action